Overexpression of the Mitochondrial Malic Enzyme Genes (malC and malD) Improved the Lipid Accumulation in Mucor circinelloides WJ11 - Fazili, Abu Bakr Ahmad; Shah, Aabid Manzoor; Albeshr, Mohammed Fahad; Naz, Tahira; Dar, Mohammad Abass; Yang, Wu; Garre, Victoriano; Fazili, Khalid Majid; Bhat, Eijaz Ahmed; Song, Yuanda (Frontiers in Microbiology, 2022)
Mucor circinelloides serves as a model organism to investigate the lipid metabolism in oleaginous microorganisms. It is considered as an important producer of γ-linolenic acid (GLA) that has vital medicinal benefits. In this study, we used WJ11, a high lipid producing strain of M. circinelloides (36% w/w lipid, cell dry weight, CDW), to examine the role in lipid accumulation of two mitochondrial malic enzyme genes malC and malD. Homologous overexpression of both malC and malD genes enhanced the total lipid content of WJ11 by 41.16% and 32.34% respectively. In parallel, the total content of GLA was enhanced by 16.73 % and 46.76% in malC and malD overexpressing strains, respectively, because of the elevation of total lipid content. The fact that GLA content was enhanced more in the strain with lower lipid content increase, and vice versa, indicated that engineering of mitochondrial malic enzymes altered the fatty acid profile. Our results reveal that mitochondrial malic enzyme has an important role in lipid metabolism and suggest that future approaches may involve simultaneous overexpression of distinct malic enzyme genes to further boost lipid accumulation.